2020
DOI: 10.1002/cne.24964
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish visual system transmits dimming information via multiple segregated pathways

Abstract: Vertebrate retinas contain circuits specialized to encode light level decrements. This information is transmitted to the brain by dimming-sensitive OFF retinal ganglion cells (OFF-RGCs) that respond to light decrements with increased firing. It is known that OFF-RGCs with distinct photosensitivity profiles form parallel visual channels to the vertebrate brain, yet how these channels are processed by first-and higher order brain areas has not been well characterized in any species. To address this question in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
(82 reference statements)
2
12
0
Order By: Relevance
“…A dim-sensitive cluster (blue, Figure 3A ), responsive both to dims and full looms, contained the fewest ROIs, and these were principally spread across the habenulae, thalamus, tectum, and pallium, consistent with previous observations ( Cheng et al, 2017 ; Zhang et al, 2017 ; Chen et al, 2018 ; Heap L. A. L. et al, 2018 ; Robles et al, 2021 ). On average, these ROIs also had very weak responses to checkerboard stimuli.…”
Section: Resultssupporting
confidence: 88%
“…A dim-sensitive cluster (blue, Figure 3A ), responsive both to dims and full looms, contained the fewest ROIs, and these were principally spread across the habenulae, thalamus, tectum, and pallium, consistent with previous observations ( Cheng et al, 2017 ; Zhang et al, 2017 ; Chen et al, 2018 ; Heap L. A. L. et al, 2018 ; Robles et al, 2021 ). On average, these ROIs also had very weak responses to checkerboard stimuli.…”
Section: Resultssupporting
confidence: 88%
“…We propose that the unique wiring geometry of the TL-PyrN circuit serves to degrade topographic precision to generate PyrNs with large visual RFs. TL receives visual input from tectum via TLPNs, visually responsive tectal neurons with small dendrites in SFGS that project to TL (Robles et al, 2020). Single cell labeling of TLPNs has confirmed that their axons form a coarse topographic projection to TL (DeMarco et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…In the case of larval zebrafish, some of this information is already encoded in retinal ganglion cells as they arrive in the tectal neuropil, including motion-and size-specific retinal ganglion cells that terminate in the superficial and intermediate layers of the neuropil 118,120 , and retinal ganglion cells encoding a drop in luminance (dim-specific retinal ganglion cells) in deeper layers 42,120 . These 'OFF' retinal ganglion cells present different sensitivity profiles and segregate this information in the neuropil, which in turn is received by OFF-sensitive tectal cells 123 . Additionally, dim-sensitive thalamic neurons project into the deep neuropil layers 93 .…”
Section: Reviewmentioning
confidence: 99%